2021
DOI: 10.5902/2179460x43819
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization, toxicity, antioxidant and antimicrobial activity of the essential oils of Hymenaea courbaril L. and Syzygium cumini (L.) Skeels

Abstract: This study evaluated the antimicrobial, antioxidant and toxicity activity of essential oils (EOs) of Hymenaea courbaril L. var. courbaril bark and Syzygium cumini (L.) Skeels leaves. The EOs were extracted by hydrodistillation and chemically characterized by gas chromatography coupled to mass spectrometry (GC/MS). The ABTS and DPPH assay were used to evaluate antioxidant activity. For the toxicity assay, lethality was evaluated against Artemia salina Leach. For the antimicrobial assay, the method of Disc Diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Other researches have registered inhibitory and bactericidal activity of the EOSC against S. aureus [ 35 ], the species was also susceptible to the extract of the seeds of S. cumini [ 36 ]. Against E. coli, the EOSC showed low inhibition when tested previously [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other researches have registered inhibitory and bactericidal activity of the EOSC against S. aureus [ 35 ], the species was also susceptible to the extract of the seeds of S. cumini [ 36 ]. Against E. coli, the EOSC showed low inhibition when tested previously [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The preference for treatments using S. cumini is acceptable given its proven low toxicity, as evidenced in the studies by Everton et al [36] and Everton et al [33]. These studies found that EOSC does not exhibit significant toxicity towards the model organism Artemia salina.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial activity has been reported in the essential oil of S. cumini leaves, tested against clinically relevant bacterial strains such as Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. These factors highlight the importance of S. cumini in medicine and pharmaceutical research as a product with potential to provide therapeutic benefits [33].…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Everton et al 25 demonstrated the antimicrobial activity of Citrus sinensis essential oil due to the efficacy of its main component, d-limonene, in inhibiting Staphylococcus aureus by the Disc Diffusion Method. Together with the components of thyme essential oil they form good barriers against microorganisms.…”
Section: Aerobic Mesophilic Microorganismsmentioning
confidence: 99%